Sleeve Gastrectomy Surgery Improves Glucose Metabolism by Downregulating the Intestinal Expression of Sodium–Glucose Cotransporter-3. Issue 1 (2nd January 2022) - Ren, Yixing; Zhao, Zhiming; Zhao, Guodong; Liu, Qu; Wang, Zizheng; Liu, Rong
Abstract: Aims: Sleeve gastrectomy (SG) has been proven effective in the treatment of obesity and type 2 diabetes. We hypothesized that SGLT3 may play an important role in the mechanism of glucose control and weight loss after SG. Materials and methods: Daily body weight and food intake were measured in SG and sham-operated mice. Glucose tolerance test, SGLT3 agonist (αMG), and SGLT1 inhibitor (phlorizin) perfusion experiments were used to detect changes in intestinal SGLT3 and SGLT1 activity following SG. Expression of SGLT3a and SGLT1 was assessed at 2 weeks, 1 month after surgery by quantitative PCR and fluorescence immunoassay. Hematoxylin and eosin staining was used to detect morphological changes in the villi. SGLT3 and SGLT1 expression was measured after stimulation of human intestinal epithelial cells (HIEC). Results: Both the body weight and daily food intake of the SG-treated mice decreased within 30 days after surgery. Oral glucose absorption was significantly reduced at 30 days. The intestinal stimulation proved that SG can improve glucose metabolism, which can be reversed by αMG and enhanced by phlorizin. Villus height and surface area of the intestine in SG mice decreased after surgery. mRNA expression of SGLT3a and SGLT1 decreased at 2 weeks and 1 month after SG, immunofluorescence also confirmed these changes. HIEC stimulation confirmed that αMG could increase the expression of SGLT3 and SGLT1, but the expression of SGLT1 was down regulated when phlorizin was added to the medium. Conclusion: The results suggest that reducing SGLT3 expression might contribute to lowering blood glucose and controlling body weight after SG.